One Night Project: Creating Memorable Vibes Through a Dangdut Koplo Event - Frizqy Afia Grandi; Rafly Ananda Yanuar; Wita Arthawidya; Siti Khumayah; Dedet Erawati (Publikasi Indonesia, 2025)
In recent years, dangdut koplo has emerged as a significant cultural phenomenon in Indonesia, particularly among youth audiences. This music genre’s popularity stems from its energetic rhythms, viral social media presence, and interactive performance style. Against this backdrop, event organizers face growing challenges in creating memorable experiences that resonate with modern audiences. This research aims to analyze the strategies employed by event organizer One Night Project in creating a memorable atmosphere or vibe at dangdut koplo events. Using a qualitative approach, this study explores various elements that shape the audience experience, such as artist selection, stage design, use of lighting and sound technology, and interaction between the audience and organizers. This research employs customer experience theory and atmosphere theory. Data was collected through in-depth interviews with organizers, audience members, sponsors, and media partners involved in several One Night Project events. The findings reveal that the synergy between carefully curated elements of music, visuals, and social interaction can enhance audience emotional engagement, creating a lively and memorable atmosphere. Additionally, social media plays a crucial role in amplifying the event’s impact through documentation and digital interactions before, during, and after the concert. These findings offer practical insights for entertainment industry practitioners, particularly those organizing dangdut koplo music events, in developing effective and impactful audience experience strategies.